Pewarisan Berbagai Karakter Kuantitaif Varietas Kedelai (Glycine Max L.) Di Bawah Naungan Kelapa Sawit Muda - Apryana Cresensia; Aslim Rasyad (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2022)
Soybean is one of the commodities that are very much processed by the people of Indonesia. Soybean production in Indonesia in recent years has tended to decline, so efforts can be made to increase the productivity of soybean plants. Efforts are made by planting soybeans on replanted land in oil palm plantations. The aim of the study was to determine the response of various soybean varieties to shade caused by the canopy of young oil palm trees and to determine the components of diversity and heritability of various quantitative variables of soybean plants on land conditions that were shaded by young oil palms. This research was conducted using a split plot design (RPT) which consisted of 2 factors. The first plot is shaded conditions according to the age of oil palm plants N1 (control), N2 (3 years old oil palm) and N3 (5 years old oil palm) and the subplots are six soybean genotypes namely Anjasmoro, Agromulyo, Burangrang, Dena 1 , Grobogan and Dega 1. Parameters observed were plant height, internode length, number of primary branches, age of flowering plant, age of harvest, number of pithy pods, number of seeds per plant, weight of seeds per plant, weight of 100 seeds, yield per m2. The data obtained were analyzed using a variance test and continued with the Duncan's New Multiple Range Test (DNMRT) test at 5% level. The results showed that soybean variety Dega 1 could be recommended as a genotype that was quite well adapted to land shaded by oil palm at the age of 3 years on quantitative characters (age of flowering plant, seed weight per plant and yield per m2). Keyword : Glycine max L., Palm oil canopy, Replanting.